Historical Dictionary of Sikhism - Fenech, Louis E.; McLeod, W. H. (Lanham : Rowman & Littlefield Publishers, 2014)
This third edition of Historical Dictionary of Sikhism covers its history through a chronology, an introductory essay, and an extensive bibliography. The dictionary section has over 1000 cross-referenced entries on key persons, organizations, the principles, precepts and practices of the religion as well as the history, culture and social arrangements. This book is an excellent access point for students, researchers, and anyone wanting to know more about Sikhism.
Description based upon print version of record.
Includes bibliographical references.
Editor's Foreword; Preface; Reader's Notes; Acronyms and Abbreviations; Table, Map, and Chart; Chronology; Introduction; THE DICTIONARY; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z; Bibliography; About the Authors
Keywords: Sikhism -- Dictionaries; RELIGION / Comparative Religion; Electronic books